THE LABOUR POTENTIAL AND ECONOMIC FREEDOM: THEORETICAL BASE FOR DIALECTICAL UNITY - Moroz, Volodymyr; Moroz, Mykhaylo (Ekonomika, 2012)
The content of the economic freedom as a category of modern economic knowledge and the dialectics of its correlation with the category of the personality labour potential are revealed in the article. The appropriate correlations are highlighted in the context of the authors’ model called “the conditional propeller”, the plot of which is revealed through the balance of human’s, society’s and state’s competence. Also, the article contains theoretical generalizations as regards the correlation of human “I” with the system of labour potential of a personality and gives practical recommendations concerning its consideration in the daily activities of a national government.